A sperm whale (Cetacea: Physeteroidea) from the Paraná Formation (Late Miocene) of Entre Ríos, Argentina. Environment and Taphonomy - Pérez, Leandro Martín; Cione, Alberto Luis; Cozzuol, Mario Alberto; Varela, Augusto Nicolás
Sperm whales (Physeteroidea) are known since the late Oligocene. They became very diverse during the middle and late Miocene (Bianucci and Landini, 2006). They are currently represented by only three species. Sperm whales have been reported in Argentina from the early Miocene Gaiman Formation [Diaphorocetus pouchetti Moreno, 1892, and Idiorophus patagonicus (Lydekker, 1893)], Gran Bajo del Gualicho Formation (Preaulophyseter gualichensis Caviglia and Jorge, 1980), the late Miocene Barranca Final Formation (“Aulophyseter” rionegrensis Gondar, 1975), and the late Miocene Paraná Formation (cf. Aulophyseter sp. by Agnolín and Lucero, 2004) Fil: Pérez, Leandro Martín. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleozoología Invertebrados; Argentina Fil: Cione, Alberto Luis. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Cozzuol, Mario Alberto. Departamento de Zoología, Istituto de Ciências Biológicas, Universidade Federal de Minas Gerais, Av. Antônio Carlos 6627 - Pampulha, Belo Horizonte, Brazil; Argentina Fil: Varela, Augusto Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina